Yeast cell wall extracts from Saccharomyces cerevisiae varying in structure and composition differentially shape the innate immunity and mucosal tissue responses of the intestine of zebrafish (Danio rerio) - Rawling, Mark; Schiavone, Marion; Apper, Emmanuelle; Merrifield, Daniel L.; Castex, Mathieu; Leclercq, Eric; Foey, Andrew (Frontiers in Immunology, 2023)
With the rising awareness of antimicrobial resistance, the development and use of functional feed additives (FFAs) as an alternative prophylactic approach to improve animal health and performance is increasing. Although the FFAs from yeasts are widely used in animal and human pharma applications already, the success of future candidates resides in linking their structural functional properties to their efficacy in vivo. Herein, this study aimed to characterise the biochemical and molecular properties of four proprietary yeast cell wall extracts from S. cerevisiae in relation to their potential effect on the intestinal immune responses when given orally. Dietary supplementation of the YCW fractions identified that the α-mannan content was a potent driver of mucus cell and intraepithelial lymphocyte hyperplasia within the intestinal mucosal tissue. Furthermore, the differences in α-mannan and β-1,3-glucans chain lengths of each YCW fraction affected their capacity to be recognised by different PRRs. As a result, this affected the downstream signalling and shaping of the innate cytokine milieu to elicit the preferential mobilisation of effector T-helper cell subsets namely Th17, Th1, Tr1 and FoxP3+-Tregs. Together these findings demonstrate the importance of characterising the molecular and biochemical properties of YCW fractions when assessing and concluding their immune potential. Additionally, this study offers novel perspectives in the development specific YCW fractions derived from S. cerievisae for use in precision animal feeds.